The Function of Silence in Gertrud von le Fort’s Novel “The Veil of Veronica” - Piasta, Ewa Anna Anna (Respectus Philologicus, 2014)
The German writer Gertrud von le Fort is among the leading representatives of the German Renouveau catholique – a religious and literary movement, originated in France in the 1900s. By turning to the values of an authentic Catholicism, the movement was aimed at a renewal of literature and society through faith. The subject of this article is the best known novel by Gertrud von le Fort, The Veil of Veronica, part one of which is titled The Roman Fountain, and part two – The Wreath of Angels. The objective of the present study is to analyse a variety of aspects and functions of silence, as seen in the novel The Veil of Veronica as well as to prove the assumption that this phenomenon is found both in the language layer of the text through direct reference or indirect implication, and in the layer of meaning, when used to highlight specific affections of the characters and to suggest what is not conveyed by language. The analysis is preceded by a theoretical introduction, in which the author defines the phenomenon of silence on the basis of the existing literature, focusing on its multiple meanings and functions. The analysis of the novel enables to argue that silence can mean understanding, a complete lack thereof, be an expression of refusal to communicate verbally, as well as an attitude of readiness to listen. In each of these cases, it is a form of communication. Silence is frequently related to profound experiences of literary characters and provides a means to intensify artistic expression. Silence is also connected with religious practice, as it arises from the experience of the sacred, which is of particular significance in the novel.